Economic vs. ecological benefit for organic food: the role of perceived values in online consumer reviews - Huo, Hong; Yao, Junru; Li, Qiutong; Wu, Rong; Wang, Chen; Yu, Dingyao (Frontiers in Sustainable Food Systems, 2025)
IntroductionWith the growing awareness of sustainable development, organic food has been favored by consumers due to its advantages in both human health and environmental sustainability. However, the economic and ecological values of organic food have been two factors that consumers weigh. Online reviews, as an important source of data for capturing consumers’ perceived value, especially the temporal information of reviews, provide new opportunities for revealing the dynamic impact of consumers’ perceived value on satisfaction.MethodsBased on 63,674 online reviews, this study utilizes structural topic modeling to identify the specific dimensions of consumers’ perceptions of economic and ecological values of organic food, and incorporates multiple linear regression modeling to explore the specific effects of these perceived values on consumer satisfaction and their dynamic trends.ResultsThe results of the study indicate that consumers’ perceptions of both economic and ecological values significantly enhance their satisfaction with organic food. Further, this study found that the positive effect of perceived ecological value on consumer satisfaction increased over time, while the positive effect of perceived economic value on consumer satisfaction gradually weakened.DiscussionThis study theoretically provides a new research idea to identify consumer perceived value based on online review data, and reveals the dynamic impact of perceived value on satisfaction, adding a new perspective for sustainable consumption research. Practically, this study provides an important reference for the marketing and product optimization of the organic food industry, especially in terms of dynamic consumer behavior analysis and market positioning.